Palavras no chão: murmurações e vozes em Minas Gerais no século XVIII - Gaspar, Tarcísio de Souza (2008)
This work investigates the whisperings and oral voices [murmurings] transmitted in the several political and social conflicts that happened in the captaincy of Minas Gerais during the XVIII century. Were analyzed, specialy, the rumors spreaded during the Emboabas' War, the Mutinies of Caeté and Barra do Rio das Velhas, the Revolt of Vila Rica, the Backcountry's Riots, the conspiracies of the pombaline period and, finally, the Minas' Conspiracy of 1789.